Trends in shark bycatch research: current status and research needs - Molina, Juan Manuel; Cooke, Steven J. (Reviews in Fish Biology and Fisheries)
Over the last few decades, much effort has been devoted towards quantifying and reducing bycatch in marine fisheries. Of late, there has been a particular focus on sharks given that bycatch is a frequently listed threat for sharks on the International Union for the Conservation of Nature Red List. However, currently there are no quantitative reviews or syntheses that explore the issue of shark bycatch globally which is problematic given that such a synthesis could inform conservation actions and identify pressing research gaps. We performed a qualitative and quantitative survey of the peer-reviewed literature to characterize trends in shark bycatch research with a particular goal of identifying research needs and opportunities. Using a structured literature review we identified 103 papers that met our search criteria, with the first one published in 1993. Early research efforts focused on documenting the scope of bycatch (i.e., determining that sharks were indeed captured as bycatch), but more recently there have been increased efforts devoted to developing and evaluating bycatch reduction strategies for sharks. Research activity was most common in the North Atlantic (~ 40% of the total articles analysed) with comparatively less research in other areas such as the Indo-Pacific region where shark bycatch is regarded as particularly common and problematic. Most studies were observational with comparatively fewer experimental and modeling studies, and even fewer that combined research approaches. Gear modifications (e.g., hook size and type for long lines, net size and mesh design for nets) were the most commonly evaluated strategy for reducing shark bycatch; however, development and use of techniques like repellents, or seasonal area closures, or a combination of strategies, offer interesting possibilities that require further study. In addition, although many sharks are discarded, little is known about post-release survival or sub-lethal consequences of fisheries interactions, or evaluations of different fish ...